2020
DOI: 10.1039/d0cc05812b
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of cobalt through fluorescence changes in β-cyclodextrin-bimane complexes

Abstract: A supramolecular complex of syn-(methyl,methyl)bimane (1) and β-cyclodextrin demonstrates a sensitive (limit of detection = 0.60 nM) and selective fluorescence turn-off response in the presence of cobalt in aqueous media,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…Interestingly, introducing the iodine analyte to a solution of compound 1 complexed with β‐cyclodextrin (1 : 1 water: acetonitrile) led to highly similar photophysical responses (see ESI for more details), with iodine‐induced decreases in the fluorescence emission spectrum and increases in the UV‐visible absorption spectrum. This result is in contrast to what we observed for the detection of cobalt using a complex formed between bimane 2 and β‐cyclodextrin, where complexation caused a marked improvement in solution‐state fluorescence detection [17] . We speculate that this differential behavior of the cyclodextrin‐bimane complexes for the different bimane fluorophores is likely due to the fact that bimane 1 binds β‐cyclodextrin predominantly around the triazole termini ( vide infra for 1 H NMR confirmation), and that the bimane core which is responsible for the analyte‐induced fluorescence changes is largely unaffected.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, introducing the iodine analyte to a solution of compound 1 complexed with β‐cyclodextrin (1 : 1 water: acetonitrile) led to highly similar photophysical responses (see ESI for more details), with iodine‐induced decreases in the fluorescence emission spectrum and increases in the UV‐visible absorption spectrum. This result is in contrast to what we observed for the detection of cobalt using a complex formed between bimane 2 and β‐cyclodextrin, where complexation caused a marked improvement in solution‐state fluorescence detection [17] . We speculate that this differential behavior of the cyclodextrin‐bimane complexes for the different bimane fluorophores is likely due to the fact that bimane 1 binds β‐cyclodextrin predominantly around the triazole termini ( vide infra for 1 H NMR confirmation), and that the bimane core which is responsible for the analyte‐induced fluorescence changes is largely unaffected.…”
Section: Resultscontrasting
confidence: 99%
“…Bimane as a fluorescent scaffold has a number of advantages, including its small size and high quantum yield, that make it particularly attractive for detection applications [15] . Recent joint work by our research groups has exploited the high affinity binding of bimane in β‐cyclodextrin, reported initially by Politzer and co‐workers, [16] to develop highly sensitive and selective fluorescence‐based cobalt sensors [17] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, all aqueous studies were conducted in double deionized water, so that no interference and/or fluorescence quenching occurred due to residual metal ions. Such ions, in particular palladium ( Das et al, 2016 ), sodium ( Roy et al, 2018 ), and cobalt ( Pramanik et al, 2020 ), have been shown to complex effectively to the bimane core, leading to marked changes in the bimane’s photophysical properties. Also of note, the existence of trace amounts of water even in the “0%” water is likely, based on literature precedent ( Son et al, 2001 ), but this trace amount of water is accounted for as part of the baseline for our fluorescence quenching experiments, in accordance with literature precedent ( Porter and Markham 1970 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports from one of our research groups have demonstrated the development of high-performance fluorometric ( Haynes and Levine 2020 ) and colorimetric ( Haynes et al, 2019 ) sensors for a variety of organic and inorganic analytes. Moreover, recent successes in novel sensor development have been reported in joint publications from our research groups, and demonstrate that bimane-based supramolecular constructs act as highly effective sensors for cobalt (II) ions ( Pramanik et al, 2020 ) and for molecular iodine ( Pramanik et al, 2021 ). These sensors, which operate in both solution-state and on filter papers to provide fluorometric and colorimetric analyte detection, have notable practical advantages, including their high sensitivity, ease of access, and non-toxicity of both the bimane transducing element and supramolecular cyclodextrin scaffold.…”
Section: Introductionmentioning
confidence: 92%